Tinjauan Yuridis terhadap Asuransi Jiwa dalam Proses Pelaksanaan Penyelesaian Klaim Pembayaran Asuransi: Studi Putusan Nomor 111/PDT.G/2014/PN.PTK - Puspita, Aina Cahya; Novita, Tri Reni (Rechtsnormen Jurnal Komunikasi dan Informasi Hukum, 2022)
Insurance is like an umbrella that must be available before the rain arrives. No one expects disasters and misfortunes to happen to themselves and their possessions. However, disasters or events that cause losses are often unavoidable. Insurance is protection or protection for yourself and your family and property when something unexpected happens. This type of research is normative legal research with descriptive analytical research. In conducting data collection, it is done by means of library research. This literature research uses secondary legal materials and tertiary legal materials. To analyze the use of the data approach approach, namely by analyzing the data in depth and then conducting research. The results are expected to be able to answer the legal problems posed in this paper. The results of the research show that what prospective customers need to pay attention to before buying insurance products are choosing the type of protection needed, understanding checking procedures and claim requirements, being aware of the ability to pay premiums, choosing the right insurance product and company, understanding buying insurance products. to whom, for example through an agent, through bancassurance, or telemarketing. The factor that causes the insurance claim to be rejected by the insurance company is because the claim payment is not in accordance with the clauses in the insurance policy. The steps that can be taken by the customer if the insurance claim issued by the insurer is not in accordance with the agreement is to mediate or report the case to the court